IDENTIFIKASI TINGKAT KERAWANAN TANAH LONGSOR DI AJIBARANG BANYUMAS MENGGUNAKAN METODE SKORING - Hana Hanifa; Suwardi Suwardi (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Landslide is a form of natural phenomenon that often occurs in mountainous and hilly regions with steep up to very steep slopes. Landslide is the movement of slope-forming materials in the form of rocks, debris, soil or materials down the slope. This study aimed to identify the distribution of landslide-prone areas in Ajibarang, Banyumas Regency. The research was conducted by survey method. The model used to determine landslide-prone areas was the Stories Index Model approach. Analysis of geophysical factors was based on SPOT-5 image data and the Indonesia Topographical Map (RBI Map). Identification of land geophysical factors for susceptibility level was determined according to geological map, slope map, soil type map and land use map. The results showed that the level of landslide susceptibility in the study area was divided into 4 classes, namely very low (3.733,41 ha), low (3.303,73 ha), moderate (123,49 ha) and high (150,37 ha).